Faeries, Marimachas, Queens, and Lezzies: The Construction of Homosexuality Before the 1969 Stonewall Riots - Arriola, Elvia R. (Columbia Journal of Gender and Law, 1995)
The Stonewall Riots erupted on a hot night in June 1969 in New York City, when an unlikely group of revolutionaries, a few Black and Puerto Rican drag queens and butch lesbians, turned a routine bar raid into a street fight with the local police. The latter had just taken a payoff from the unlicensed bar owners and arrested the most obvious looking homosexuals. A motley crew of effeminate queers resisted what would otherwise have been a routine raid on a bar that catered to gay people. The conflict attracted an angry crowd of onlookers and supporters who fought into the night with coins, beer bottles, and sticks, and whose struggle ultimately came to symbolize the overthrow of decades of official harassment, repression, and degradation. A simple street fight on June 27th, 1969, changed history and breathed life into the then dormant and internally conflicted homophile movement. In recent years, gays and lesbians have staked out their deserved place in the annals of American legal, social, and political history with a growing body of social and historical accounts of the Stonewall Riots’ and of the pre-Stonewall gay world. Typically, these revisionist histories briefly mention the constant threat of raids and harassment that dictated the closeted lifestyle of most gays and lesbians before the riots. References to the police raids, or to the Riots themselves, however, do not often examine the various social forces converging on that moment when a seedy working-class bar in Manhattan’s West Village, which openly served homosexuals and outrageously dressed Black and ethnic drag queens, became the focal point of a conflict that instigated a national gay civil rights movement.